Pengaruh Politik Domestik terhadap Dinamika Bantuan Luar Negeri Chile - Achsin, Muhaimin Zulhair; Sisilia, Eveline (Faculty of Economics and Social Science, Department of International Relations, Universitas Amikom Yogyakarta, 2020)
One of the most significant changes in foreign aid issues has been the emerging of several non-tradional donors as providers of foreign aid. One of these new emerging donor countries is Chile, the top five economies (GDP) in Latin America, one of the two of OECD Latin America members, and one of upper-middle income countries. Chile government started designing the foreign aid agency in 1990 through AGCI (The Chilean International Co-operation Agency), in a democracy transition era from Pinochet to Aylwin. This research attempts to analyze how Chile domestic political factors influence changes in the dynamics of Chile’s ODA (Official Development Assistance), from aid-recipient to aid-provider. By using a theory from Lancester, the results are the domestic political factors namely ideas, institutions, interests (interest groups), and organizations influence the dynamic of Chile’s foreign aid. However, the major obstacle in early phase of developing the agendas was coming from the military.